Genome-wide identification, expression and function analysis of the MTP gene family in tulip (Tulipa gesneriana) - Lu, Jiaojiao; Xing, Guimei; Zhang, Yanqiu; Zhang, Huihua; Wu, Tianyu; Tian, Zengzhi; Qu, Lianwei (Frontiers in Plant Science, 2024)
Currently, soil heavy metal contamination is a severe issue, particularly with Cd pollution. The metal tolerance protein (MTP) proteins, as plant divalent cation transporters, play a crucial role in the transport and tolerance of heavy metals in plants. This study conducted comprehensive identification and characterization of the MTP gene family in the tulip. A total of 11 TgMTP genes were identified and phylogenetically classified into three subfamilies. Conserved motif and gene structure analyses unveiled commonalities and variations among subfamily members. Expression profiling demonstrated several TgMTPs were markedly upregulated under Cd exposure, including the TgMTP7.1. Heterologous expression in yeast validated that TgMTP7.1 could ameliorate Cd sensitivity and enhance its tolerance. These results provide primary insights into the MTP gene family in tulip. Phylogenetic relationships and functional analyses establish a framework for elucidating the transporters and molecular mechanisms governing Cd accumulation and distribution in tulip. Key TgMTPs identified, exemplified by TgMTP7.1, may illuminate molecular breeding efforts aimed at developing Cd-tolerant cultivars for the remediation of soil Cd contamination.